A companion to business ethics - Frederick, Robert (Malden, Mass. : Blackwell Publishers, 1999)
'In a series of articles specifically commissioned for this volume, business ethicists survey the main areas of interest and concern in the field of business ethics.'--BOOK JACKET.'The book can be used as a comprehensive text for introductory or advanced courses in business ethics, as a reference for teachers and writers in the field, or as a guide for other academic or business persons who wish to become familiar with the central issues in the field. To enhance its usefulness as a reference work, the volume includes bibliographies of the relevant literature, a list of internet sources for material on business ethics, and an extensive index.'--Jacket.
Business Ethics and Normative Theories -- A Kantian approach to business ethics / Norman E. Bowie -- Utilitarianism and business ethics / Milton Snoeyenbos, James Humber -- Business ethics and virtue / Robert C. Solomon -- Social contract approaches to business ethics: bridging the'is-ought' gap / Thomas W. Dunfee, Thomas Donaldson -- Business ethics and the pragmatic attitude / Douglas R. Anderson -- An outline of ethical relativism and ethical absolutism / Robert E. Frederick -- Feminist theory and business ethics / Robbin Derry -- Business ethics in a free society / Tibor R. Machan -- Nature and business ethics / William C. Frederick -- Toward new directions in business ethics: some pragmatic pathways / Sandra B. Rosenthal, Rogene A. Buchholz -- Business ethics: pragmatism and postmodernism / R. Edward Freeman, Robert A. Phillips -- Business Ethics and the Business Disciplines -- Ethics in management / Archie B. Carroll -- Finance ethics / John R. Boatright -- Ethics in the public accounting profession / Mohammad J. Abdolmohammadi, Mark R. Nixon -- Marketing ethics / George G. Brenkert -- Law, ethics, and managerial judgment / Lynn S. Paine -- Business ethics and economics / Diane L. Swanson -- Business ethics and the social sciences / Linda Klebe Trevino -- Issues in Business Ethics -- International business ethics / Richard T. de George -- Corporate moral agency / John R. Danley -- Employee rights / Ronald Duska -- Business ethics and work: questions for the twenty-first century / Joanne B. Ciulla.
Includes bibliographical references and index.
Print version record.
Keywords: Business ethics; Morale des affaires; BUSINESS & ECONOMICS -- Business Ethics; Business ethics; Business ethics; Bedrijfsethiek; Morale des affaires; Electronic books